Does good local governance improve subjective well-being? - Ana Cárcaba; Rubén Arrondo; Eduardo González Fidalgo (European Research on Management and Business Economics (ERMBE), 2022)
The goal of this research is to examine the effects of good management of local governments on individual subjective well-being (SWB). We define three dimensions of good governance at the municipal level: accountability, government efficiency and control of corruption. We use a large survey of individual welfare carried out in Spain in 2013 and 2018 and distinguish four potential drivers of SWB: socio-demographic factors, material conditions, quality of life and municipal governance. Individual QoL variables, such as social connections or health status are major drivers of SWB. To a lesser extent, the material conditions also have a significant impact. With respect to good governance, our results point to an immediate positive effect of government efficiency on individual SWB levels. In contrast, accountability, understood as transparency, does not seem to have a significant impact. Surprisingly, we find no immediate effect of corruption on reported SWB, but a very strong deferred impact.
Keywords: H75; M41; I31; I38; 650; Good governance; Municipalities; Quality of life; Spain; Subjective well-being